Immunohistochemical localization of low density lipoprotein receptor-related protein 1 and α2-Macroglobulin in retinal and choroidal tissue of proliferative retinopathies - Barcelona, Pablo Federico (2010)
The immunolocalization of the low density lipoprotein receptor-related protein 1 (LRP1) and its ligand α 2-Macroglobulin (α2M) was examined in tissues from human donor eyes of normal, diabetic and sickle cell disease subjects. Streptavidin alkaline phosphatase immunohistochemistry was performed with a mouse anti-human LRP1 and rabbit anti-human α2M antibodies. Retinal and choroidal blood vessels were labeled with mouse anti-human CD34 antibody in adjacent tissue sections. Mean scores for immunostaining from the pathological and control eyes were statistically compared.LRP1 immunoreactivity was very weak to negative in the neural retina of normal subjects except in scattered astrocytes. LRP1 expression in diabetic eyes was detected in the internal limiting membrane (ILM), astrocytes, inner photoreceptor matrix, choriocapillaris and choroidal stroma. The ligand α2M, however, was limited mainly to blood vessel walls, some areas of the inner nuclear layer (INL), photoreceptors, RPE-Bruch's membrane-choriocapillaris complex, intercapillary septa, and choroidal stroma. In sickle cell eyes, avascular and vascular retina as well as choroidal neovascularization (CNV) were analyzed. In avascular areas, LRP1 immunoreactivity was in innermost retina (presumably ILM, astrocytes, and Muller cells) and INL as well as RPE-Bruch's membrane-choriocapillaris complex and choroidal stroma α2M was very weak in avascular peripheral retina compared to vascularized areas and limited to stroma in choroid. In contrast, in areas with CNV, LRP1 immunoreactivity was significantly decreased in overlying retina and in RPE-Bruch's membrane and choroidal stroma compared to the controls, while α2M was elevated in RPE-Bruch's membrane near CNV compared to normal areas in sickle cell choroid. The mean scores revealed that LRP1 and α2M in neural retina were significantly elevated in astrocytes and ILM in diabetic eyes (p ≤ 0.05), whereas in sickle cell eyes scores were elevated in ILM and INL (p ≤ 0.05). In addition, α2M immunoreactivity was in photoreceptors in both ischemic retinopathies. In choroid, the patterns of LRP1 and α2M expression were different and not coincident.This is the first demonstration of the presence of LRP1 and α2M in human proliferative retinopathies. Elevated LRP1 expression in sickle cell neural retina and diabetic inner retina and choroid suggests that LRP1 plays an important role in ischemic neovascular diseases.